Tuning sulfur fixation via conditioner–oxygen synergy during oxidative pyrolysis of sewage sludge under smouldering conditions - Shan Cheng; Linxi Guo; Hong Tian; Dangzhen Lv; Junjie Huang; Jiaxin Yu (Fuel, 2026)

Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Establishment and antiviral immune response characterization of fin cell lines from black carp (Mylopharyngodon piceus) and gynogenetic black carp - Wei Qin; Linxi Cai; Mengru Liu; Yu Tan; Ji Liu; Jun Yan; Jiaji Pan; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2026)

Bioinspired self-assembled gradient Janus bilayer aerogel enabling coupled solar desalination and purification of multicomponent oily emulsions - Peng Pi; Yu Feng; Wen Jung Li; Ling Pan; Youxi Lin; Linxi Hou; Zihao Huang; Qinwei Wang; Xuhui Wang; Zhiying Ren (Chemical Engineering Journal, 2026)

Long-term exposure to fine particulate matter and its constituents, genetic susceptibility, and incident bipolar disorder - Xinru Zhao; Yudiyang Ma; Ning Chen; Lei Zheng; Meiqi Xing; Feipeng Cui; Jianing Wang; Linxi Tang; Yaohua Tian; Peng Xiong; Yu Chen (Environmental Pollution, 2026)

Cadmium and Benzo[a]pyrene Co-exposure Synergistically Induces Apoptosis in Bronchial Epithelium: Mechanistic Insights and Predictive Risk Modeling for Indoor Dust - Junbo Liu; Linxi Yang; Jixiang Chen; Yu Bon Man; Ming Hung Wong; Zhang Cheng (Biological Trace Element Research, 2025)

High-temperature calcination modified red clay as an efficient adsorbent for phosphate removal from water - Kanglong Cheng; Qin You; Linxi Zou; Yu Zhang; Peng Wang; Wen Zhang (Environmental Research, 2025)

Characteristics and mechanism of winter marine heatwaves in the cold tongue region of the South China Sea - Linxi Meng; Yunwei Yan; Lei Zhang; Wen Xing; Yi Yu; Xiaogang Xing (Frontiers in Marine Science, 2024)
Marine Heatwaves (MHWs) are persistent anomalous sea surface temperature warming events that can affect the marine ecological environment and ecosystems. Here, we study the winter MHWs in the cold tongue region of the South China Sea (SCS) from 1982 to 2022. Our results show that the winter MHWs in the cold tongue region have the strongest cumulative intensity in the SCS, exceeding 45°C·day/time. These strong MHWs are due to their high mean intensity and long duration. Significant interannual variations are observed in these MHWs, with extreme MHW events occurring in the El Niño winters of 97/98 and 15/16. By employing a mixed layer heat budget analysis, we reveal that the extreme MHW event in the winter of 97/98 is caused primarily by the surface heat flux term, and secondarily by the vertical entrainment term. While the 15/16 extreme event is caused by a combination of the surface heat flux term, the vertical entrainment term and the horizontal advection term.

Long-term trends and extreme events of marine heatwaves in the Eastern China Marginal Seas during summer - Jing Xu; Yunwei Yan; Lei Zhang; Wen Xing; Linxi Meng; Yi Yu; Changlin Chen (Frontiers in Marine Science, 2024)
Marine heatwaves (MHWs) are a type of widespread, persistent, and extreme marine warming event that can cause serious harm to the global marine ecology and economy. This study provides a systematic analysis of the long-term trends of MHWs in the Eastern China Marginal Seas (ECMS) during summer spanning from 1982 to 2022, and occurrence mechanisms of extreme MHW events. The findings show that in the context of global warming, the frequency of summer MHWs in the ECMS has increased across most regions, with a higher rate along the coast of China. Areas exhibiting a rapid surge in duration predominantly reside in the southern Yellow Sea (SYS) and southern East China Sea (ECS, south of 28°N). In contrast, the long-term trends of mean and maximum intensities exhibit both increases and decreases: Rising trends primarily occur in the Bohai Sea (BS) and Yellow Sea (YS), whereas descending trends are detected in the northern ECS (north of 28°N). Influenced jointly by duration and mean intensity, cumulative intensity (CumInt) exhibits a notable positive growth off the Yangtze River Estuary, in the SYS and southern ECS. By employing the empirical orthogonal function, the spatio-temporal features of the first two modes of CumInt and their correlation with summer mean sea surface temperature (SST) and SST variance are further examined. The first mode of CumInt displays a positive anomalous pattern throughout the ECMS, with notable upward trend in the corresponding time series, and the rising trend is primarily influenced by summer mean SST warming. Moreover, both of the first two modes show notable interannual variability. Extreme MHW events in the SYS in 2016 and 2018 are examined using the mixed layer temperature equation. The results suggest that these extreme MHW events originate primarily from anomalous atmospheric forcing and oceanic vertical mixing. These processes involve an anomalous high-pressure system over the SYS splitting from the western Pacific subtropical high, augmented atmospheric stability, diminished wind speeds, intensified solar radiation, and reduced oceanic mixing, thereby leading to the accumulation of more heat near the sea surface and forming extreme MHW events.

Azole fungicides inhibit human and rat gonadal 3β-hydroxysteroid dehydrogenases: Structure-activity relationship and in silico docking analysis - Jianmin Sang; Hong Wang; Yang Yu; Zhongyao Ji; Miaomiao Xia; Ting Hao; Linxi Li; Ren-shan Ge (Food and Chemical Toxicology, 2023)

Geographical distribution of trace elements (selenium, zinc, iron, copper) and case fatality rate of COVID-19: a national analysis across conterminous USA - Ying Chen; Zheng Feei Ma; Dahai Yu; Zifei Jiang; Bo Wang; Linxi Yuan (Environmental Geochemistry and Health, 2022)

Soil Selenium Concentration and Residents Daily Dietary Intake in a Selenosis Area: A Preliminary Study in Yutangba Village, Enshi City, China - Zedong Long; Jiqian Xiang; Jiaping Song; Yapu Lu; Hongqing Yin; Yunfen Zhu; Xiaodong Liu; Liqiang Qin; Gary S. Bañuelos; Zhangmin Wang; Yu Kang; Linxi Yuan; et al. (Bulletin of Environmental Contamination and Toxicology, 2020)

Novel Long-Acting Drug Combination Nanoparticles Composed of Gemcitabine and Paclitaxel Enhance Localization of Both Drugs in Metastatic Breast Cancer Nodules - Jesse Yu; Qingxin Mu; Simone Perazzolo; James I Griffin; Linxi Zhu; Lisa A McConnachie; Danny D Shen; Rodney JY Ho (Pharmaceutical Research, 2020)

Role of AMP-activated protein kinase α1 in 17α-ethinylestradiol-induced cholestasis in rats - Xiaojiaoyang Li; Runping Liu; Lan Luo; Linxi Yu; Xin Chen; Lixin Sun; Tao Wang; Phillip B. Hylemon; Huiping Zhou; Zhenzhou Jiang; Luyong Zhang (Archives of Toxicology, 2017)

Effects of Apelin-13 on Rat Bone Marrow-Derived Mesenchymal Stem Cell Proliferation Through the AKT/GSK3β/Cyclin D1 Pathway - Lanfang Li; Lifang Li; Lu He; Zidong Zhang; Feng Xie; Yu Guo; Jianhua Xiao; Linxi Chen; Jian Li (International Journal of Peptide Research and Therapeutics, 2014)

NOX4-Derived Reactive Oxygen Species Drive Apelin-13-Induced Vascular Smooth Muscle Cell Proliferation via the ERK Pathway - Lanfang Li; Fang Li; Feng Li; Xiaohuan Mao; Li Yang; Hao Huang; Yu Guo; Linxi Chen; Jian Li (International Journal of Peptide Research and Therapeutics, 2011)